Balloon Interrogation of Intervening Tissue: A Novel Method to Decide Strategy for Closing Multiple Atrial Septal Defects. (20th September 2022) - Dalvi, Bharat; Bhalgat, Parag
Abstract : Background: Two separate ostium secundum atrial septal defects are a challenging substrate for device closure due to lack of a well-described strategy or an adequately evaluated protocol. Methods: This is a prospective study comprising 20 patients with 2 atrial septal defects who underwent device closure. All of them underwent balloon interrogation (BI) of the intervening tissue to decide 1- versus 2-device strategy. During BI, if the flow through both the defects could be stopped completely implying adequate mobility of the separating tissue, a single device strategy was used. The size of the device in this subset was determined by BI diameter. In case the flow persisted, 2 devices were used to close the defects separately. Results: The mean age was 24±17 years. The main defect size was (mean 14.5 mm±SD 2.69 mm), whereas the second defect measured (mean 8.5±SD 3.02 mm). The tissue separating the 2 defects was measured (mean 6.1±SD 2.6 mm). In 15 of them, based on the BI results, a single device was used successfully to close both the defects without a residual shunt. In the remaining 5 patients, 2 devices were used. There were no complications during the procedure or at follow-up period of 41.9±16.9 months. Conclusions: BI in patients with 2 atrial septal defects is helpful in defining 1- versus 2-device strategies and in choosing the size of the device to be used. Nearly 3/4 of the patients may get away with a single device for closing both the defects successfully thereby decreasing the cost and complexity of the procedure.